Autophagy in Mycobacterium tuberculosis and HIV infections - Espert, Lucile; Beaumelle, Bruno; Vergne, Isabelle (Frontiers in Cellular and Infection Microbiology, 2015)
Human Immunodeficiency Virus (HIV) and Mycobacterium tuberculosis (M.tb) are among the most lethal human pathogens worldwide, each being responsible for around 1.5 million deaths annually. Moreover, synergy between acquired immune deficiency syndrome (AIDS) and tuberculosis (TB) has turned HIV/M.tb co-infection into a major public health threat in developing countries. In the past decade, autophagy, a lysosomal catabolic process, has emerged as a major host immune defense mechanism against infectious agents like M.tb and HIV. Nevertheless, in some instances, autophagy machinery appears to be instrumental for HIV infection. Finally, there is mounting evidence that both pathogens deploy various countermeasures to thwart autophagy. This mini-review proposes an overview of the roles and regulations of autophagy in HIV and M.tb infections with an emphasis on microbial factors. We also discuss the role of autophagy manipulation in the context of HIV/M.tb co-infection. In future, a comprehensive understanding of autophagy interaction with these pathogens will be critical for development of autophagy-based prophylactic and therapeutic interventions for AIDS and TB.